Crystallization of myosin subfragment 1. - Rayment, I (1984)
Crystals of myosin subfragment 1 from avian skeletal muscle have been grown reproducibly. They diffract x-rays to at least 4.5-A resolution. The subfragment 1 crystallizes in space group P2(1)2(1)2(1) where a = 107 A, b = 117 A, and c = 278 A. The cell dimensions and intensity distribution on x-ray diffraction photographs are consistent with two molecules in the crystallographic asymmetric unit. Electrophoretic analysis shows that the myosin subfragment 1 present in the crystals contains a 95-kilodalton heavy chain fragment and both the essential and regulatory light chains.